Aniseikonia and Unequal Vertex Distances: A Case Report - Krebs, R.F.; Robertson, K.M. (Canadian Journal of Optometry, 2026)
A 23 year old female had complained of intolerable headaches and eyestrain experienced after only short periods of spectacle wear. Using measurements obtained on a newly designed eikonometer, a small degree of aniseikonia through her spectacles was detected. Complete correction of aniseikonia was achieved by equalizing the venex distances in front of both eyes. This was accompanied by complete cessation of her symptoms and allowed prolonged and comfonable spectacle wear.